Inflation and Labor Market Flexibility: The Squeaky Wheel Gets the Grease - Ana Maria Loboguerrero; Ugo Panizza (Inter-American Development Bank, Research Department, 2003)
Inflation can grease the wheels of the labor market by relaxing downward wage rigidity but it can also increase uncertainty and have a negative sand effect. This paper studies the grease effect of inflation by looking at whether the interaction between inflation and labor market regulations affects how employment responds to changes in output. The results show that in industrial countries with highly regulated labor markets, the grease effect of inflation dominates the sand effect. In the case of developing countries, we rarely find a significant effect of inflation on labor market regulations and provide evidence indicating that this could be due to the presence of a large informal sector and limited enforcement of de jure labor market regulations.
Keywords: 330; Inflation; Lohnrigidität; Arbeitsmarkt; Beschäftigungseffekt; Schätzung; Industrieländer; Entwicklungsländer